2007
DOI: 10.1146/annurev.micro.61.080706.093440
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Degradosome of Escherichia coli: An mRNA-Degrading Machine Assembled on RNase E

Abstract: The RNA degradosome of Escherichia coli is a multiprotein complex involved in the degradation of mRNA. The principal components are RNase E, PNPase, RhlB, and enolase. RNase E is a large multidomain protein with an N-terminal catalytic region and a C-terminal noncatalytic region that is mostly natively unstructured protein. The noncatalytic region contains sites for binding RNA and for protein-protein interactions with other components of the RNA degradosome. Several recent studies suggest that there are alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
433
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(442 citation statements)
references
References 82 publications
4
433
0
5
Order By: Relevance
“…RNase E is considered the rate-limiting enzyme for the degradation of many mRNAs 48 and for rRNA decay during carbon starvation and quality control. 24 It is also a major endoribonuclease in tRNA 49 and rRNA 50 maturation.…”
Section: Ribonuclease Ementioning
confidence: 99%
See 1 more Smart Citation
“…RNase E is considered the rate-limiting enzyme for the degradation of many mRNAs 48 and for rRNA decay during carbon starvation and quality control. 24 It is also a major endoribonuclease in tRNA 49 and rRNA 50 maturation.…”
Section: Ribonuclease Ementioning
confidence: 99%
“…24 It is also a major endoribonuclease in tRNA 49 and rRNA 50 maturation. Furthermore, RNase E is a core member of the degradosome which is a multiprotein complex involved in RNA degradation 48 assembled on RNase E through PNPase, RhlB, and enolase binding to the C-terminal half of RNase E. 51-53 The degradosome is effective in structured RNA decay from duplex unwinding by the helicase RhIB. 54 For these reasons, we investigated whether RNase E may be involved in tRNA degradation after amino acid starvation.…”
Section: Ribonuclease Ementioning
confidence: 99%
“…Recently, it was shown that a dominant-negative mutation in motif VI of dbpA results in a ribosome biogenesis defect (Elles and Uhlenbeck, 2008). While the above proteins are involved in ribosome biogenesis, the RhlB protein is part of the degradosome, a multicomponent complex involved in the targeted degradation of a large subset of mRNAs (Carpousis, 2007;Py et al, 1996). The RNA helicase in this complex is associated on the scaffold protein RNase E and is generally assumed to assist the degradosome on structured RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hfq protects poly(A) tails from degradation by the exoribonucleases RNase II and polynucleotide phosphorylase (PNPase), and the endoribonuclease RNase E (28). The latter two enzymes are members of the degradosome, a multicomponent assembly that is responsible for RNA decay in bacteria (32). Hfq has been shown to interact with polynucleotide phosphorylase (PNPase), which adds AG-rich polynucleotide tails to the 3Ј ends of mRNAs that are terminated in a Rho-independent fashion, and RNase E, the key endoribonuclease involved in RNA destruction (27)(28)(29)-both presumably via protein-RNA-protein interactions (33).…”
mentioning
confidence: 99%